Assessing the equilibrium of food supply and demand in China’s food security framework: a comprehensive evaluation, 1980–2017 - Wei, Yujun; Fang, Dan; Wei, Xiaokun; Ye, Zhonghua (Frontiers in Sustainable Food Systems, 2024)
The continuous upward trajectory observed in total grain production serves as a fundamental pillar for guaranteeing food security. Nevertheless, relying solely on the measurement of China’s overall food security status through total grain output is inherently biased and neglects to capture the comprehensive nature of food security. This study adopts a food supply and demand balance perspective and constructs an evaluation indicator system for food security based on indicators such as grain yield per unit area, per capita grain possession, grain inventory, and inventory ratio. The weight of each indicator in the food security system is calculated using the entropy value method, and a comprehensive evaluation of China’s food security level from 1980 to 2017 is conducted. The study revealed that China’s food supply and demand exhibited a discernible upward trajectory in development. Notably, the food supply demonstrated greater volatility, whereas the food demand remained relatively stable but experienced incremental growth. Between approximately 1985 and 1993, China’s food supply and demand subsystem briefly experienced a state of mild imbalance, followed by a state of moderate imbalance around 2003. These imbalances were primarily attributed to insufficient effective food supply. In terms of the equilibrium between supply and demand in the context of food security, China’s food supply and demand exhibit a predominantly balanced condition with a slight surplus, wherein the adequacy of food supply significantly influences food security. Furthermore, the provision of policy support serves as a robust assurance for food security, and China’s existing policy framework for food security demonstrates a constructive impact.